Penerapan Model Pembelajaran Problem Solving Dalam Meningkatkan Hasil Belajar IPS Siswa SD - Sitti Jauhar; Makmur Nurdin (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2017)
The problem in this research is the low of IPS learning result of fourth grader of Inpres 3/77 Manurunge Sub District Tanete Riattang Bone Regency. The problem can be formulated as follows "How is the implementation of Problem Solving learning model in Improving Results IPS Student Learning Class IV Primary Inpres 3/77 ManurungeTaneteRiattang District Bone District? The purpose of this research is to describe the application of Problem Solving learning model in Improving Learning Outcomes of Social Studies IPS IV Primary School Inpres 3/77 ManurungeTaneteRiattang District Bone District. Focus in Action Research This class is the Application of Problem Solving learning model and IPS Learning Outcomes. The subjects of the study were the fourth grade students of SD Inpres 3/77 Manurunge, data collection techniques in this study were Observation and Test. Techniques Data analysis is data reduction, Data presentation, Conclusion drawing. The result of the research that the application of Problem Solving learning model can improve the learning result of IPS of fourth grade students of SD Inpres 3/77 Manurunge Kecamatan Tanete Riattang Bone District.